Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VI. The bigeminata species group, with descriptions of seven new species - Wang, Shuxia; Liu, Chen (Zootaxa, 2019)
The bigeminata species group of the genus Promalactis Meyrick, 1908 is proposed to include seven new species here described which share similarities in the forewing pattern: P. bigeminata sp. nov., P. derecta sp. nov., P. pectinacea sp. nov., P. pileata sp. nov., P. scalpelliformis sp. nov., P. ventericoncava sp. nov., and P. venteriprocessa sp. nov. Photographs of adults and genitalia of the new species are provided.